The routledge companion to aesthetics - Gaut, Berys; Lopes, Dominic (London/New York Routledge, 2013)
The third edition of the acclaimed Routledge Companion to Aesthetics contains over sixty chapters written by leading international scholars covering all aspects of aesthetics.